The Effects of Various Acid Catalyst on the Esterification of Jatropha Curcas Oil based Trimethylolpropane Ester as Biolubricant Base Stock - Noor Hafizah Arbain; Jumat Salimon (E-Journal of Chemistry)
Biolubricant production of trimethylolpropane ester (ET) was conducted via esterification of fatty acid (FA) of Jatropha curcas oil with trimethylolpropane (TMP). The condition for this reaction was as follows: temperature was 150 °C, time of reaction was 3 hours, molar ratio of FA: TMP was 4:1 and 2% wt/wt concentrated catalyst (based on weight of FA). Different catalyst was used in this reaction such as perchloric acid, sulfuric acid, p-toluenesulfonic acid, hydrochloric acid and nitric acid. The composition of ET was determined by Gas Chromatography (GC-FID). The ester group was confirmed by Fourier Transform Infrared Spectroscopy (FTIR) and the structure was confirmed by proton and carbon Nuclear Magnetic Resonance (1H-NMR and 13C-NMR) spectra. 70% of ET was successfully synthesized using perchloric acid in this research. The pour point of the product was observed as low as –23 °C, flash point is >300 °C and viscosity index is 150.